كێلە گۆڕە نەخشێندراوەكانى محەممەد تەقى بەگ لە گوندى جام ڕێز لە شارۆچكەى سەنگاو - حمەعارف, پ.ى. د. زريان سالار; مجيد, ڕزگار جەواد (Sulaimani Journal for Humanities, 2023)
This research is entitled (the carved gravestones of Mohammad Taqi Bag cemetery in Jamriz village of Sangaw township, an artistic field research). It focuses on the history and Islamic civilization of Sangaw area where most of the gravestones are broken due to natural and human causes and that have been analyzed. The research relies on theoretical and oral history and then the comparative archaeological sciences. The research is the result of several field visits to Sangaw area. The researcher encountered several problems, the most obvious of which is the lack of accurate and necessary resources about the area, but The researcher attributes the importance of the subject to the fact that the keys of the gravestones in Islamic archeology are important archaeological and material remains that have their own historical and archaeological value, because They are documents of personal identity and uniqueness of the time in many ways, including (religious, political, cultural, social, economic, military and artistic, etc.) domains.
Keywords: Key Words Jamriz; Tomb tombstone Tomb side Decoration